Pengaruh Konsentrasi Nutrisi AB Mix Terhadap Pertumbuhan Dan Produksi Tanaman Pakcoy (Brassica Rapa Var. Chinensis L.) Menggunakan Sistem Hidroponik Sumbu (Wick System) - Anindya Aulia Putri (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2025)
This research aims to determine the effect of providing AB Mix nutrition on the growth and production of pakcoy plants. The research was carried out in the researcher's own home, namely on Jalan Santun number 30, Sudirejo 1 District, Medan City, North Sumatra Province. The type of research is experimental research using a Completely Randomized Non-Factorial Design with a total of 5 treatments and 5 replications with a total sample of 25 holding tanks with a total of 125 plants. The parameters observed were plant height, number of leaves, leaf length and weight per plant after harvest. Data were analyzed using Analysis of Variance (Anova) followed by the Duncan Advanced Test (DMRT). The research results showed that AB Mix nutrition had a real influence on the growth and production of pakcoy plants (Brassica rapa var chinensis L.), the best plant growth was in treatment A3 (30 ml) with plant height at 5 WAP as high as 24 cm, number of leaves 22 strands, leaf length 20 cm and plant weight 39.6 gr. The dose that showed optimum results for the growth and production of lettuce plants was obtained in treatment A3 (30 ml).